Republicano no Império, Monarquista na República: a trajetória intelectual de Afonso Celso (1892-1938) - Conti, Viviane Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Compreender a trajetória intelectual de Afonso Celso (1860-1938) é o objetivo central desta dissertação. Para isso, com auxílio da História da Historiografia e da História Intelectual, foram analisadas a sua produção historiográfica e as questões envolvidas nela, como as temáticas abordadas, as ideias e concepções marcantes, além das problemáticas envolvidas diretamente na sua forma de escrever história e as funções institucionais ocupadas por ele. A trajetória de Afonso Celso como escritor foi iniciada quando ele era ainda um jovem poeta, contudo, a publicação de Vultos e Factos e sua entrada no Instituto Histórico e Geográfico Brasileiro (IHGB) em 1892, representou a transição dele para o ofício do historiador. A partir disso, a sua atuação enquanto intelectual foi marcada por uma polivalência, ocupando diversas funções em diferentes instituições. Aqui, privilegiamos a sua atuação no IHGB, associação que presidiu de 1912 até 1938, quando faleceu, e que representou o principal lugar de produção historiográfica no período.

Understanding the intellectual contributions of Afonso Celso (1860-1938) is the central objective of this dissertation. For this, with the help of the History of Historiography and Intellectual History, his historiographic production and the issues involved in it were analyzed, such as the themes addressed, the ideas and outstanding concepts, in addition to the problems directly involved in his way of writing history and the institutional functions occupied by him. Afonso Celso's trajectory as a writer began when he was still a young poet, however, the publication of Vultos e Factos and his entry into the Brazilian Historical and Geographical Institute in 1892, represented his transition to the historian's craft. From this, his performance as an intellectual was marked by versatility, occupying different functions in different institutions. Here, we privilege his work at the IHGB, an association that he presided over from 1912 until 1938, when he died, and which represented the main place of historiographical production in the period.
Republican in the Empire, Monarchist in the Republic: the intellectual trajectory of Afonso Celso (1892-1938)
Keywords: Afonso Celso; IHGB; Historiografia brasileira; Brazilian historiography